2012
DOI: 10.1200/jco.2012.30.15_suppl.7522
|View full text |Cite
|
Sign up to set email alerts
|

EGFR compound mutants and survival on erlotinib in non-small cell lung cancer (NSCLC) patients (p) in the EURTAC study.

Abstract: 7522 Background: When EGFR compound mutants (exon 19 deletions or L858R plusT790M) are present at the time of clinical resistance to erlotinib, patients attain longer overall survival (OS) (Oxnard et al. CCR 2011). The H1975 cell line, harboring L858R plus T790M prior to treatment, is sensitive to gefitinib (Sordella et al. Science 2004; Faber et al. Cancer Discovery 2011), though the compound mutant may become dominant after multiple passages in vitro, leading to resistance (Pao et al. PLoS Med 2005). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In a retrospective analysis of the EURTAC trial, which compared the efficacy of erlotinib versus chemotherapy in patients with EGFR-mutant lung cancer, the median OS of patients with a preexisting T790M mutation was found to be superior to that of patients without a preexisting T790M mutation in both treatment groups. 16 However, in the study by Su et al, there was no difference in survival noted between patients with or without the T790M mutation. 13 In contrast to prior studies, the current study revealed that patients with T790Mnegative tumors had inferior survivals compared with patients with T790M-positive tumors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a retrospective analysis of the EURTAC trial, which compared the efficacy of erlotinib versus chemotherapy in patients with EGFR-mutant lung cancer, the median OS of patients with a preexisting T790M mutation was found to be superior to that of patients without a preexisting T790M mutation in both treatment groups. 16 However, in the study by Su et al, there was no difference in survival noted between patients with or without the T790M mutation. 13 In contrast to prior studies, the current study revealed that patients with T790Mnegative tumors had inferior survivals compared with patients with T790M-positive tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Chemotherapy), which used TaqMan assay in the presence of a peptide nucleic acid clamp, detected the mutation in 47 of 123 patients (38.2%). 15,16 More recently, Su et al provided data regarding the T790M mutation frequency by using a next-generation sequencing (NGS) method as a validation test. 13 In that study, the investigators compared mass spectrometry (MS) genotyping assays with standard direct sequencing in terms of the ability to detect T790M mutations present at a low frequency in tissue samples obtained before and after EGFR-TKI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…After prolonged exposure to EGFR-TKIs, the T790M mutant allele becomes enriched, resulting in AR to EGFR-TKIs (1). Rosell et al (5) reported that among AR NSCLC patients, T790M-positive patients had better outcomes (longer PFS and OS) than T790M-negative patients when treated with chemotherapy, indicating that tumors with AR due to the T790M mutation are more sensitive to chemotherapy. Kuo et al (4) observed that patients with AR to EGFR-TKIs Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that chemotherapy efficacy may depend on the underlying mechanisms of AR to EGFR-TKIs. Rosell et al (5) observed that in patients with secondary T790M, tumors were more sensitive to Sensitivity to chemotherapeutics of NSCLC cells with acquired resistance to EGFR-TKIs is mediated by T790M mutation or epithelial-mesenchymal transition chemotherapeutic drugs, thus prolonging progression-free survival (PFS) and overall survival (oS). In contrast, NSCLC cells with EMT and patients with EMT-positive tumors were less sensitive to chemotherapy or radiotherapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that patients who acquired the EGFR T790M mutation after TKI therapy had longer survival, suggesting that the T790M mutation may be related to indolent biology and slow tumor growth [ 32 , 33 ]. In the EURTAC (EURopean TArceva vs Chemotherapy) study, the survival of patients with a pre-existing T790M mutation was superior to that of patients without it [ 34 ]. Fujita et al .…”
Section: Discussionmentioning
confidence: 99%